The Effectiveness of Schema Therapy on Frustration Tolerance, Emotional Regulation, and Maladaptive Early Schemas in Students - Mohamadzadeh, Franak; Vatankhah, Hamidreza; Banisi, Parinaz (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to investigate the effectiveness of schema therapy on frustration tolerance, emotional regulation, and maladaptive early schemas in students in 2020.Methods and Materials: This study employed a quasi-experimental design using a pretest-posttest approach with a control group. The statistical population included all high school second-grade students in Tehran, from which 30 participants were selected using purposive sampling and randomly assigned to the experimental group (n = 15) and the control group (n = 15). The experimental group underwent schema therapy in eight 90-minute sessions, while the control group remained on a waitlist. The study utilized the Frustration Discomfort Scale (Harrington, 2005), the Cognitive Emotion Regulation Questionnaire (Garnefski & Kraaij, 2006), and the Young Schema Questionnaire (Young, 1998) for data collection, administered during the pretest and posttest phases. Data analysis was performed using SPSS version 24, incorporating both descriptive and inferential statistics (analysis of covariance).Findings: The findings indicated that schema therapy had a significant effect on the components of frustration tolerance in students. Furthermore, schema therapy had a significant effect on the components of cognitive emotional regulation in students. Additionally, schema therapy demonstrated a significant effect on the components of maladaptive early schemas in students.Conclusion: Based on the findings, it can be concluded that schema therapy is an effective and sustainable approach to improving the psychological conditions of students.